Maxillofacial Fractures in the Province of Terni (Umbria, Italy) in the Last 11 Years: Impact of COVID-19 Pandemic. Issue 8 (26th November 2022) - Spallaccia, Fabrizio; Vellone, Valentino; Colangeli, Walter; De Tomaso, Silvia
Abstract : The main purpose of this retrospective study is to analyze the main causes and the main anatomical structures involved in maxillofacial traumas in the province of Terni, Umbria. From January 2009 to July 2021, 603 patients were admitted with a maxillofacial trauma diagnosis and underwent surgery at "Santa Maria Hospital" in Terni, Italy. The collected data included sex, age, nationality, cause of trauma, type of fractures, comorbidities, clinical signs, symptoms, date of admission, and date of discharge from the hospital. Causes were divided into 5 categories: road traffic accidents, accidental falls, physical assault, sport accidents, and occupational injuries. Men were more involved than women, with a male:female ratio of 325:1. The mean age of the population was 41.7 years. The main cause of trauma were road traffic accidents (36%), followed by accidental falls (27%), an increasing phenomenon during the current SARS-CoV-2 global pandemic. The orbital floor was the most fractured anatomical site, followed by zygoma and nasal bones.